Populasi dan Serangan Hama Polong Kedelai Etiella zinckenella (Treitschke) (Lepidoptera: Pyralidae) yang Diperlakukan dengan Insektisida Berbahan Aktif Klorpirifos 500 g/l dan Sipermetrin 50 g/l - RUSYANA, NGAKAN PUTU MEIKA; BAGUS, I GUSTI NGURAH; SUNARI, ANAK AGUNG AYU AGUNG SRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.2, April 2018, 2018)
Population and Attack of Soybean pods Etiella zinckenella (Treitschke) (Lepidoptera: Pyralidae) treated Insecticide with Activity Klorpirifos 500 g/l and Sipermetrin 50 g/l The study was conducted to find out the Population and Attack of Soybean pods, Etiella zinckenella (Treitschke) (Lepidoptera: Pyralidae) treated Insecticide with Activity Klorpirifos 500 g/l and Sipermetrin 50 g/l. This research was conducted in Gunaksa Village, Dawan District, Klungkung Regency, from December 2016 until February 2017. The purpose of this research is to know the effect of insecticide active ingredient (Klorpirifos 500 g/l and Sipermetrin 50 g/l) to soybean pest the populations of and the rate of E. zinckenella pests on soybean crops. This study used a randomized block design (RBD), with five treatment levels (concentration) and five replications. The results showed that insecticide with chlorpyrifine 500 g/l and sipermetrin 50 g/l at concentration 1.50 ml/l were able to suppress E. zinckenella and increase production.